Kode Etik dan Integritas Profesi Advokat: Hubungan antara Etika, Pengawasan, dan Pembelaan Diri dalam Praktik Hukum (Jurnal Pendidikan dan Bahasa Sastra Harapanan, 2026)
Keywords:Code of Ethics, Advocate Integrity, Supervision, Self-Defense, Rule of Law. This study aims to analyze the relationship between the code of ethics, supervisory mechanisms, and the right of self-defense within the professional practice of advocates in Indonesia. The main problems examined include: (1) how the code of ethics shapes the integrity of advocates; (2) the extent to which ethical supervision by the Honorary Council is effective; and (3) how the mechanism of self-defense ensures the fulfillment of procedural justice in ethical proceedings. This research employs a normative juridical method, using statutory approaches, conceptual analysis of professional ethics, and literature review based on the works of scholars such as Soerjono Soekanto, Muhammad Thahir Azhary, and Munir Fuady. The findings indicate that the enforcement of the code of ethics cannot be separated from a strong supervisory structure and a fair mechanism for self-defense. The code of ethics establishes moral standards, supervision ensures compliance, and self-defense guarantees a balanced and just ethical process that does not violate the rights of advocates. In conclusion, the synergy among these three elements forms an essential foundation for strengthening the integrity of the legal profession and enhancing public trust in the justice system and the principles of the rule of law.